Synthesis of 3,3-oxaspirocycles via cobalt-catalyzed cascade C-H activation and carboamidation of alkynes - Bholanath Garai; Molla Rahamat Ali; J. Richard Premkumar; Basker Sundararaju (Communications Chemistry)
Abstract Spirocyclic motifs are increasingly recognized as privileged scaffolds in drug discovery due to their unique three-dimensional architecture and favorable pharmacokinetic properties. Despite significant progress in the synthesis of carbo- and hetero-spirocycles, efficient methods for constructing oxa-spirocyclic frameworks remain underdeveloped. We present a one-step, cobalt(III)-catalyzed protocol for the synthesis of oxa-spirocyclic compounds using phenoxy acetamide and alkynes. The reaction is highly versatile, accommodating a range of functional groups on the aromatic ring and providing spirocyclic products in good to excellent yields. Substitutions at the quinone ring or internal alkyne prevent further cyclization, leading exclusively to the 1,2-carboamidated product. The carboamidation protocol is extended to unactivated olefins, and the subsequent acid-mediated post-synthetic modifications allow for the generation of complex three-dimensional structures. Kinetic studies and DFT calculations identify migratory insertion as the rate-determining step, with acetic acid assisting in the oxidative addition of the N–O bond and protodemetalation. This work provides a robust and efficient strategy for synthesizing oxa-spirocyclic compounds, showcasing the potential of cobalt(III) catalysis in complex molecular synthesis.